Transverse momentum dependence of D-meson production in Pb-Pb collisions at √sNN=2.76 TeV Pb-Pb collisions - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klein, Jochen; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; et al. (Journal of high energy physics, 2016)
The production of prompt charmed mesons D0, D+ and D∗+, and their antiparticles, was measured with the ALICE detector in Pb-Pb collisions at the centre-of-mass energy per nucleon pair, sNN$$ \sqrt{s_{NN}} $$, of 2.76 TeV. The production yields for rapidity |y| < 0.5 are presented as a function of transverse momentum, pT, in the interval 1-36 GeV/c for the centrality class 0-10% and in the interval 1-16 GeV/c for the centrality class 30-50%. The nuclear modification factor RAA was computed using a proton-proton reference at s=2.76$$ \sqrt{s}=2.76 $$TeV, based on measurements at s=7$$ \sqrt{s}=7 $$TeV and on theoretical calculations. A maximum suppression by a factor of 5-6 with respect to binary-scaled pp yields is observed for the most central collisions at pT of about 10 GeV/c. A suppression by a factor of about 2-3 persists at the highest pT covered by the measurements. At low pT (1-3 GeV/c), the RAA has large uncertainties that span the range 0.35 (factor of about 3 suppression) to 1 (no suppression). In all pT intervals, the RAA is larger in the 30-50% centrality class compared to central collisions. The D-meson RAA is also compared with that of charged pions and, at large pT, charged hadrons, and with model calculations.
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, J. Klein, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F.Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 955 weitere]
Gesehen am 30.07.2020